Circular RNA erythrocyte membrane protein band 4.1 assuages ultraviolet irradiation-induced apoptosis of lens epithelial cells by stimulating 5’-bisphosphate nucleotidase 1 in a miR-24-3p-dependent manner - Cuiyun Zhou (Taylor & Francis Group, 2021)
Apoptosis of lens epithelial cells contributed to the formation of age-related cataract (ARC), and previous data revealed that circular RNA (circRNA) was responsible for the underneath mechanism. The study was organized to explore the role of circular RNA erythrocyte membrane protein band 4.1 (circ_EPB41) in ultraviolet (UV) irradiation-induced apoptosis of lens epithelial cells. SRA01/04 cells were irradiated with UV to mimic the ARC cell model. The RNA levels of circ_EPB41, microRNA-24-3p (miR-24-3p), and 3ʹ(2ʹ), 5ʹ-bisphosphate nucleotidase 1 (BPNT1) were detected by quantitative real-time polymerase chain reaction. Protein expression was checked by western blot. 5-Ethynyl-29-deoxyuridine, 3-(4,5-Dimethylthazol-2-yl)-2,5-diphenyltetrazolium bromide and DNA content quantitation assays were performed to investigate cell proliferation. Flow cytometry was conducted to analyze cell apoptosis. Dual-luciferase reporter assay was implemented to confirm the interaction among circ_EPB41, miR-24-3p, and BPNT1. Our data showed that circ_EPB41 and BPNT1 expression were downregulated in ARC tissues and UV-irradiated SRA01/04 cells as compared with normal anterior lens capsules and untreated SRA01/04 cells. Circ_EPB41 overexpression ameliorated the effects of UV irradiation on the proliferation and apoptosis of SRA01/04 cells. Besides, miR-24-3p, a target miRNA of circ_EPB41, attenuated circ_EPB41 introduction-mediated proliferation, and apoptosis of UV-irradiated SRA01/04 cells. MiR-24-3p regulated UV irradiation-induced effects by targeting BPNT1. Importantly, it was found that circ_EPB41 stimulated BPNT1 production by miR-24-3p. Taken together, the enforced expression of circ_EPB41 ameliorated UV irradiation-induced apoptosis of lens epithelial cells by miR-24-3p/BPNT1 pathway, providing us with a potential target for the therapy of UV-caused ARC.